State of the Art in Biosensors General Aspects - Rinken, Toonika (IntechOpen, 2013)
As biosensors comprise a prospective alternative to traditional chemical analyses, enabling fast on- and in-line measurements with sufficient selectivity, the field is expanding rapidly and is offering new ideas and developments every day. This book aims to cover the present state of the art in the biosensor technology and introduce the general aspects of biosensor- based techniques and methods. The book consists of 13 chapters by 44 authors and is divided into 3 sections, focused on bio-recognition techniques, signal transduction methods and signal analysis.